Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let's work through the problems step-by-step.
### Part a
Given:
[tex]\[ x = 7^{a - b} \][/tex]
[tex]\[ y = 7^{b - a} \][/tex]
To show that [tex]\(x \cdot y = 1\)[/tex]:
[tex]\[ x \cdot y = 7^{a-b} \cdot 7^{b-a} \][/tex]
Using properties of exponents:
[tex]\[ 7^{a-b} \cdot 7^{b-a} = 7^{(a-b) + (b-a)} \][/tex]
Simplifying the exponent:
[tex]\[ 7^{(a-b) + (b-a)} = 7^0 \][/tex]
Since any non-zero number raised to the power of 0 is 1:
[tex]\[ 7^0 = 1 \][/tex]
Thus:
[tex]\[ x \cdot y = 1 \][/tex]
### Part b
Given:
[tex]\[ x + y = x \][/tex]
We need to show that [tex]\( x^y = 1 \)[/tex].
Since [tex]\( x + y = x \)[/tex], subtract [tex]\( x \)[/tex] from both sides:
[tex]\[ y = 0 \][/tex]
Any non-zero number raised to the power of 0 is 1:
[tex]\[ x^y = x^0 = 1 \][/tex]
Thus:
[tex]\[ x^y = 1 \][/tex]
### Part c
Given:
[tex]\[ a = 2 \][/tex]
[tex]\[ b = 1 \][/tex]
We need to show that:
[tex]\[ (a+b)^2 = a^2 + 2ab + b^2 \][/tex]
First, calculate [tex]\( (a+b)^2 \)[/tex]:
[tex]\[ (2 + 1)^2 = 3^2 = 9 \][/tex]
Now calculate the right-hand side:
[tex]\[ a^2 + 2ab + b^2 \][/tex]
[tex]\[ 2^2 + 2(2)(1) + 1^2 \][/tex]
[tex]\[ 4 + 4 + 1 = 9 \][/tex]
Both sides are equal:
[tex]\[ 9 = 9 \][/tex]
Thus:
[tex]\[ (a+b)^2 = a^2 + 2ab + b^2 \][/tex]
### Part d
Given:
[tex]\[ a = 5 \][/tex]
[tex]\[ b = 3 \][/tex]
We need to show that:
[tex]\[ (a-b)^2 = a^2 - 2ab + b^2 \][/tex]
First, calculate [tex]\( (a-b)^2 \)[/tex]:
[tex]\[ (5 - 3)^2 = 2^2 = 4 \][/tex]
Now calculate the right-hand side:
[tex]\[ a^2 - 2ab + b^2 \][/tex]
[tex]\[ 5^2 - 2(5)(3) + 3^2 \][/tex]
[tex]\[ 25 - 30 + 9 = 4 \][/tex]
Both sides are equal:
[tex]\[ 4 = 4 \][/tex]
Thus:
[tex]\[ (a-b)^2 = a^2 - 2ab + b^2 \][/tex]
### Part e
Given:
[tex]\[ p + q + r = 0 \][/tex]
We need to show that the expression [tex]\[ x^{p+q} \times x^{p-q} \times x^{q+r} \times x^{q-r} \times x^{r+p} \][/tex]
simplifies to 1.
Using properties of exponents:
[tex]\[ x^{p+q} \times x^{p-q} \times x^{q+r} \times x^{q-r} \times x^{r+p} = x^{(p+q) + (p-q) + (q+r) + (q-r) + (r+p)} \][/tex]
Simplifying the exponent:
[tex]\[ (p+q) + (p-q) + (q+r) + (q-r) + (r+p) \][/tex]
Combining like terms:
[tex]\[ p + q + p - q + q + r + q - r + r + p \][/tex]
Grouping all similar terms together:
[tex]\[ (p + p + p) + (q + q - q + q) + (r + r - r) \][/tex]
[tex]\[ 3p + 2q - q + q + 2r - r \][/tex]
[tex]\[ 3p + q + r \][/tex]
Since [tex]\( p + q + r = 0 \)[/tex]:
[tex]\[ 3p + q + r = 3(p + q + r) \][/tex]
[tex]\[ 3 \times 0 = 0 \][/tex]
Thus:
[tex]\[ x^{0} = 1 \][/tex]
Therefore, we have shown that:
[tex]\[ x^{p+q} \times x^{p-q} \times x^{q+r} \times x^{q-r} \times x^{r+p} = 1 \][/tex]
This covers all parts of the given problem statement.
### Part a
Given:
[tex]\[ x = 7^{a - b} \][/tex]
[tex]\[ y = 7^{b - a} \][/tex]
To show that [tex]\(x \cdot y = 1\)[/tex]:
[tex]\[ x \cdot y = 7^{a-b} \cdot 7^{b-a} \][/tex]
Using properties of exponents:
[tex]\[ 7^{a-b} \cdot 7^{b-a} = 7^{(a-b) + (b-a)} \][/tex]
Simplifying the exponent:
[tex]\[ 7^{(a-b) + (b-a)} = 7^0 \][/tex]
Since any non-zero number raised to the power of 0 is 1:
[tex]\[ 7^0 = 1 \][/tex]
Thus:
[tex]\[ x \cdot y = 1 \][/tex]
### Part b
Given:
[tex]\[ x + y = x \][/tex]
We need to show that [tex]\( x^y = 1 \)[/tex].
Since [tex]\( x + y = x \)[/tex], subtract [tex]\( x \)[/tex] from both sides:
[tex]\[ y = 0 \][/tex]
Any non-zero number raised to the power of 0 is 1:
[tex]\[ x^y = x^0 = 1 \][/tex]
Thus:
[tex]\[ x^y = 1 \][/tex]
### Part c
Given:
[tex]\[ a = 2 \][/tex]
[tex]\[ b = 1 \][/tex]
We need to show that:
[tex]\[ (a+b)^2 = a^2 + 2ab + b^2 \][/tex]
First, calculate [tex]\( (a+b)^2 \)[/tex]:
[tex]\[ (2 + 1)^2 = 3^2 = 9 \][/tex]
Now calculate the right-hand side:
[tex]\[ a^2 + 2ab + b^2 \][/tex]
[tex]\[ 2^2 + 2(2)(1) + 1^2 \][/tex]
[tex]\[ 4 + 4 + 1 = 9 \][/tex]
Both sides are equal:
[tex]\[ 9 = 9 \][/tex]
Thus:
[tex]\[ (a+b)^2 = a^2 + 2ab + b^2 \][/tex]
### Part d
Given:
[tex]\[ a = 5 \][/tex]
[tex]\[ b = 3 \][/tex]
We need to show that:
[tex]\[ (a-b)^2 = a^2 - 2ab + b^2 \][/tex]
First, calculate [tex]\( (a-b)^2 \)[/tex]:
[tex]\[ (5 - 3)^2 = 2^2 = 4 \][/tex]
Now calculate the right-hand side:
[tex]\[ a^2 - 2ab + b^2 \][/tex]
[tex]\[ 5^2 - 2(5)(3) + 3^2 \][/tex]
[tex]\[ 25 - 30 + 9 = 4 \][/tex]
Both sides are equal:
[tex]\[ 4 = 4 \][/tex]
Thus:
[tex]\[ (a-b)^2 = a^2 - 2ab + b^2 \][/tex]
### Part e
Given:
[tex]\[ p + q + r = 0 \][/tex]
We need to show that the expression [tex]\[ x^{p+q} \times x^{p-q} \times x^{q+r} \times x^{q-r} \times x^{r+p} \][/tex]
simplifies to 1.
Using properties of exponents:
[tex]\[ x^{p+q} \times x^{p-q} \times x^{q+r} \times x^{q-r} \times x^{r+p} = x^{(p+q) + (p-q) + (q+r) + (q-r) + (r+p)} \][/tex]
Simplifying the exponent:
[tex]\[ (p+q) + (p-q) + (q+r) + (q-r) + (r+p) \][/tex]
Combining like terms:
[tex]\[ p + q + p - q + q + r + q - r + r + p \][/tex]
Grouping all similar terms together:
[tex]\[ (p + p + p) + (q + q - q + q) + (r + r - r) \][/tex]
[tex]\[ 3p + 2q - q + q + 2r - r \][/tex]
[tex]\[ 3p + q + r \][/tex]
Since [tex]\( p + q + r = 0 \)[/tex]:
[tex]\[ 3p + q + r = 3(p + q + r) \][/tex]
[tex]\[ 3 \times 0 = 0 \][/tex]
Thus:
[tex]\[ x^{0} = 1 \][/tex]
Therefore, we have shown that:
[tex]\[ x^{p+q} \times x^{p-q} \times x^{q+r} \times x^{q-r} \times x^{r+p} = 1 \][/tex]
This covers all parts of the given problem statement.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.